The Influence Of Financial Management Training For Micro, Small And Medium Enterprises In Padang Sakti Lhokseumawe - M. Haykal; M. Nazaruddin; Deassy Siska; Jubaidah; Taufiq (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
As micro, small and medium entity (EMKM) business actors, we should be proud, because EMKM in Indonesia contributes to economic growth with an achievement of 60%. Especially during the COVID-19 pandemic like now. EMKM can be one of the hopes for reducing the number of unemployed in Indonesia, as well as opening up new job opportunities. The first important role of EMKM is as a means of alleviating small communities from poverty. The main reason is the high rate of employment by EMKM. EMKM also has a very important role in the economic distribution of society. In contrast to large companies, EMKM has locations in various places. High attention must be given to these EMKM actors as a manifestation of the government in supporting the economy of the common people. Moreover, EMKM is able to have a direct impact on people's lives in the lower sector to improve people's welfare. MSME development is one of the government's efforts to expand business opportunities for new entrepreneurs so that they are able to compete in services and trade. Higher education as a formal institution is expected to act as a source of learning and give full attention to EMKM as a form of partnership in developing science and technology. The role of tertiary institutions is not in providing capital but rather in fostering the ability of small industries so as to encourage the ability of small industries to access capital and business management. EMKM business development and training in this program will be carried out in one of the villages in Muara Satu District, precisely in Padang Sakti village, as one of Malikussaleh University's fostered villages. This activity is expected to increase the entrepreneurial spirit, train skills in managing a business and is expected to have a direct impact on the management of EMKM management to improve welfare in the future.